The Anxiety of Educational Reform and Innovation: Bridging of Top-Down and Bottom-Up Strategies within Practice Educational Reform of Curriculum in Indonesia - Beni Setiawan (Studies in Philosophy of Science and Education, 2020)
Reform and innovation are important issues in the educational field. Education is dynamic and changing depends on globalization demands. To counterbalance for these changes, there are two strategies to make education change. Top down and bottom up strategies. Top down and bottom up have advantages and disadvantages to the reform and innovation of educational. For instance, the advantage of top-down is the government have the power to make policy, do research about national curriculum and implement that policy in the education area, especially at school but for making policy, regulation, research and implement government have spent more money without significant result. In another hand, the benefit of bottom-up is the innovation of education easily to find and grow up because they have involved directly in the change in school, also understand what they need in education because the teachers and the principle have strong connection with the students and indirectly evaluate the national curriculum which is appropriate or not. Nevertheless, school community as the representative of bottom-up did not have the power to bring that innovation in the top level because there is no connecting purpose between government and school. In addition, the big effect is the top-down, bottom-up has the different points of view to look into education. Furthermore, to solve that problem, there are some approaches could be bond to both strategies such as the collaborative, negotiate, conceptual, and strategic clarification, school-based management and strong site councils. Based on several previous researchers that approach is the best option for bridging the educational purpose between top down and bottom up.